Thorium(IV) removal by nano olive pomace and its nano biochar: A comparative study - Akram I. Abu Shawer; Fawwaz I. Khalili; Ehab A. Hamzeh (Adsorption Science & Technology)
This study aimed to investigate the behavior of nano olive pomace as a raw adsorbent and its biochar in adsorbing thorium (IV) ions (Th(IV)) from aqueous solutions. The study also evaluated and compared their adsorption capacity, removal, optimum adsorption conditions, as well as adsorption kinetics and isotherms. Both adsorbents were characterized by thermal gravimetric analysis, differential thermal analysis, Fourier transform infrared, scanning electron microscope, X-ray diffraction, Brunauer–Emmett–Teller (BET), elemental analysis, specific surface area, bulk density, pore volume, cation-exchange capacity, and pH pzc . The effects of initial concentration, initial pH, adsorbent dosage, contact time, and temperature on the adsorption onto olive pomace and biochar were investigated using the batch method. A pseudo-second-order kinetic model controlled the adsorption of Th(IV) ions, as shown by the kinetic analysis. The Langmuir isotherm best presented the isothermal data for olive pomace and biochar. The maximum Th(IV) adsorption capacities onto olive pomace and biochar were obtained as 68.0 and 154 mg/g at pH 4.0 and 45.0°C, respectively. The adsorption of Th(IV) onto olive pomace and biochar was an endothermic (positive ΔH°), spontaneous (negative ΔG°), and random process (positive ΔS°). After column adsorption, Th(IV) ions were recovered by treating the loaded biochar and olive pomace with 1.0 or 0.1 M HNO 3 . The first and second stages of recovery employing 1.0 M HNO 3 produced the highest recovery percent of Th(IV). The results showed that these adsorbents can be utilized effectively and affordably to extract Th(IV) ions.